‎PEMBIASAAN SIKAP TANGGUNG JAWAB SEJAK DINI DALAM KEORGANISASIAN SANTRI: STUDI PENDIDIKAN AKUNTABILITAS DI PESANTREN DARUL HIJRAH MARTAPURA - Rivaldo, Rahmad (Tarbawi, 2025)
This study aims to analyze the implementation of accountability education by the Santri Care Section of the Santri Organization of Pondok Darul Hijrah (OSDA) in Cindai Alus, Martapura. Through a qualitative approach with observation, interview, and documentation study techniques. This study reveals that the accountability coaching process is carried out systematically through weekly meetings, organizational audits, and annual accountability reports (LPJ). The findings show that accountability education that is implemented has a significant impact on strengthening the character of students in terms of responsibility, discipline, honesty, and leadership skills. The pesantren environment based on Islamic values and the active involvement of educators are key factors in the success of this coaching process. This research provides conceptual and practical contributions in the development of accountability-based character education models in Islamic educational institutions, and is relevant in supporting the implementation of Law No. 18/2019 on Pesantren. In general, accountability education carried out by the Santri Care Section has proven to be able to create a professional, transparent, and responsible santri organization environment, which in turn strengthens the role of pesantren as an institution for the formation of a generation with integrity.